Analisis Perencanaan Kebutuhan Tenaga Kerja dalam Mencapai Target Produksi pada PT. ABC President Indonesia Cabang Karawang - Tasya Fadillah Zaenal; Resya Dwi Marselina; Nadira Yuniar; Novitri Lestari; Desna Girsang (Journal of Economics, Management, and Accounting, 2026)
This study aims to analyze workforce planning in support of achieving production targets at PT. ABC President Indonesia’s Karawang Branch. The study employs a qualitative approach using a case study design. Primary data was obtained through in-depth interviews with the Head of the Research and Development (R&D) Department, while secondary data was sourced from organizational documents, job descriptions, and the company’s operational reports. Data analysis was conducted through data reduction, data presentation, and drawing conclusions using source and document triangulation techniques to ensure the credibility of the findings. The research results indicate that workforce planning is conducted systematically through workload analysis, work time measurement, and the application of the Full-Time Equivalent (FTE) method to determine the appropriate workforce size aligned with production capacity. The application of this method enables the company to identify conditions of overload or underload on production lines, thereby allowing for more effective workforce distribution. The findings also indicate that the achievement of production targets is influenced by the alignment between workforce capacity, machine capacity, and operational control mechanisms. The integration of workforce planning with the production target validation process contributes to improved operational efficiency, reduced production bottlenecks, and the sustainability of company performance.